Radiation research to determine local tumor invasion in patients with cervical cancer - Bakai, O.A.; Golovko, T.S.; Ganich, A.V.; Gavriluk, O.N.; Ashykhmin, A.V. (Experimental Oncology, 2023)
Summary. The main task of radiation study of verified cervical cancer (CC) is tumor spread assessment because of its profound effect on the treatment tactics choice and prognosis. The Aim of the study was radiation study optimizing for tumor local spread assessment in patients with CC via comparing the usefulness of different magnetic resonance imaging (MRI) based approaches. Materials and Methods: 62 patients with CC were examined by MRI on tomograph 1.5 Т using contrast enhancement and diffusion-weighted imaging (DWI). Pre-operation data on radiation diagnostics of tumor spread were compared with surgical and pathologic data. Results: The diagnostic efficiency of different methods of radiation testing for assessment of local tumor spread in patients with CC was determined. The use of contrast enhancement didn’t increase an informative value of МRI in assessment of local tumor spread. False overestimation of tumor spread was caused by intense accumulation of contrast substance around the tumor due to inflammation. Use of DWI allowed to reduce the number of false positive results, and significantly increased the efficiency of MRI (p < 0.05): the positive predictive value, sensitivity, specificity and accuracy were 83.3; 90.9; 96.0 and 95.1%, respectively. Conclusions: The use of DWI increases informativeness of МRI in assessment of local tumor spread.